Study of the locomotion of a hexapod using CoppeliaSim and ROS - Coelho, Joana (2021)
Generating adaptive locomotion has seen a growing interest for the design of hexapods due to improving the autonomy of these robots, allowing them to execute tasks in more demanding environments. Data from the robot’s surrounding must be acquired and processed to adjust the locomotion, and aid with the actuation of the six limbs. This paper aims at using force sensors placed on the feet of a hexapod to control the changes of the gait phase of each limb. These sensors also assist in the search of new footholds when no contact forces are established with the ground. The system is tested in a smooth irregular terrain with obstacles, steps, and ramps, using CoppeliaSim and ROS (Robot Operating System), to dynamically evaluate the behavior of the hexapod.